Risk Assessment in a Chemical Storage Facility - Boykin, Raymond F.; Freeman, Raymond A.; Levary, Reuven R. (Management Science, 1984)
A risk assessment was performed to assist in the evaluation of equipment improvements for a chemical storage facility. The risk assessment was accomplished through the use of several different methodologies e.g., fault tree analysis, event trees, and risk perspective techniques. The result of the study was a new alternative for a chemical storage facility. This new alternative eliminated the requirement for a large storage facility and reduced the capital project cost by over 10 million dollars.